Burnout Riot Police Officers: Emotional Regulation and Five Trait Personality as Predictor - Putri Sri Wahyuni; Fransisca Iriani Roesmala Dewi (Universitas Katolik Soegijapranata, 2020)
This study examines the role of emotional regulation and five trait personality towards burnout. Personality consists of five types, namely openness, agreeableness, extraversion, conscientiousness and neuroticism. Emotional regulation consists of cognitive reappraisal and expressive suppression. Burnout consists of emotional exhaustion, personal accomplishment, and depersonalization. The subjects were riot police officers from Jakarta Regional Police. The sampling methods used were purposive sampling and convenience sampling. The respondents in this study were 79 men. This study found that emotional regulation and five trait personality contribute as much as 70.9% towards the burnout ofJakarta Regional Police riot police officers. Members of riot police who experience burnout tend to show low emotional regulation and high neuroticism.